TGR5-mediated lateral hypothalamus-dCA3-dorsolateral septum circuit regulates depressive-like behavior in male mice - Li, Xu-Yi; Zhang, Shi-Ya; Hong, Yi-Zhou; Chen, Zhi-Gang; Long, Yan; Yuan, Dan-Hua; Zhao, Jia-Jia; Tang, Su-Su; Wang, Hao; Hong, Hao (Neuron (Cambridge, Mass.), 2024)
Although bile acids play a notable role in depression, the pathological significance of the bile acid TGR5 membrane-type receptor in this disorder remains elusive. Using depression models of chronic social defeat stress and chronic restraint stress in male mice, we found that TGR5 in the lateral hypothalamic area (LHA) predominantly decreased in GABAergic neurons, the excitability of which increased in depressive-like mice. Upregulation of TGR5 or inhibition of GABAergic excitability in LHA markedly alleviated depressive-like behavior, whereas down-regulation of TGR5 or enhancement of GABAergic excitability facilitated stress-induced depressive-like behavior. TGR5 also bidirectionally regulated excitability of LHA GABAergic neurons via extracellular regulated protein kinases-dependent Kv4.2 channels. Notably, LHA GABAergic neurons specifically innervated dorsal CA3 (dCA3) CaMKIIα neurons for mediation of depressive-like behavior. LHA GABAergic TGR5 exerted antidepressant-like effects by disinhibiting dCA3 CaMKIIα neurons projecting to the dorsolateral septum (DLS). These findings advance our understanding of TGR5 and the LHAGABA→dCA3CaMKIIα→DLSGABA circuit for the development of potential therapeutic strategies in depression. [Display omitted] •LHA GABAergic neurons are involved in depression-related state•TGR5 regulates LHA GABAergic excitability through ERK-dependent Kv4.2 channel•TGR5 modulates depressive-like behavior via LHAGABA→CA3CaMKIIa→DLSGABA triple circuit Li et al. uncover that the increase in bile acid TGR5 membrane-type receptor in the lateral hypothalamic area improves depressive-like behavior and reveal a potential therapeutic strategy, activating TGR5 by supplementing bile acids for depression.